The application status quo of sports biomechanics in China's gymnastics training - Li, S.; Dan, A. (Proceedings of the 2015 International Conference on Education Technology and Economic Management, 2015)
By using the methods of literature and conference discussion, this essay has comprehensive summarized the application status quo of sports biomechanics in China's gymnastics training. The results show that: the application of sports Biomechanics in gymnastics training has been made some achievements, mainly reflected in scientific and technological services of high level sports teams. Based on the characteristics of items, and adopt qualitative and quantitative analysis to constantly pour internal drive for the development of China's gymnastics.